Producción de hidrógeno verde a partir de agua de producción petrolera (2024)
The main objective of this study is to evaluate the effect of the oil content of oilfield production water on the production of green hydrogen by electrolysis in the presence of carbon quantum dots (CQDs). For this purpose, various electrochemical techniques, such as linear sweep voltammetry (LSV), cyclic voltammetry (CV), and potentiometry were used to identify the effect of crude oil during hydrogen production. The results show that the use of CQDs affects the Faradaic efficiency, which increases from 78% to 83% with the incorporation of CQDs. In the presence of CQDs, the effects generated by the presence of the oil are inhibited at low oil concentrations. On the contrary, hydrogen production increases by 10.0% (0.1 ml/min) with a faradaic efficiency of 83% and a half-cell efficiency of 41%, compared to the record obtained with the maximum concentration of emulsified crude oil (400 mg/L). Thermogravimetric analysis (TGA), mass spectrometry (MS), and Fourier-transform infrared spectroscopy (FTIR) were employed to discern the adsorption of crude oil onto the electrodes, quantify the gas fractions generated during the process, and identify the functional groups present at the conclusion of the procedure, respectively. The size of the initial emulsion droplets was 3.4 µm, at the end of the test there was evidence of complete breakage of the emulsion due to the effect of the applied electric field. No evidence of adsorption of crude oil on graphite electrodes during electrolysis is observed based on the tests. It has been shown that green hydrogen production from crude oil production water is feasible due to the proposed of a disruptive electrolyte in the produced water which inhibite the effect of the oil content in the O/W emulsion. This allows the implementation of a new green energy production initiative aligned with the global goal of achieving net zero emissions (NZE) by 2050. The current investigation presents a prospective alternative for harnessing the 18 kW electrical energy potential employed within emulsion-breaking processes within a Colombian field for treatment around of 1000 bblopd. This alternative offers a theoretical potential for hydrogen production, approximating 7.6 kW, thus representing a promising opportunity for practical field deployment.